الواقعية الاجتماعية في مسرحية وقع الأحذية المتعبة لسليم بتقة - مسعي أحمد, إيمان; زربيط, حنان; دنيا, خماس; بن ناصر, نجوى (My University, 2024)
وقع الأحذية المتعبة مسرحية للأكاديمي سليم بتقة .محور بحثنا وقد كنا قد وقفنا عند مختلف الأزمات التي تشكل بصورة أو بأخرى واقع المجتمع الجزائري عل وجه مخصوص .حين أراد أن يعلن ثورة ضد كل ما يحد من حريته ويقلل مساحة تحرره.هي دراسة من مجموع الدراسات التي تصب في البحث والتنقيب عما يجعل النص يتكلم واقعا اجتماعيا The Weary Shoes" is a play by the academic Salim Battat. The focus of our research is this play, and we have examined the various crises that shape, in one way or another, the reality of Algerian society in particular. When the author wanted to declare a revolution against everything that limits his freedom and reduces the scope of his emancipation, this play is one of the studies that contribute to the research and exploration of what makes the text speak about social reality.
دراسات أدبية